1992
DOI: 10.1111/j.1365-2583.1993.tb00105.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a cDNA clone encoding a glycine‐rich cuticular protein of Tenebrio molitor: developmental expression and effect of a juvenile hormone analogue

Abstract: The complete sequence of a cDNA clone, isolated from epidermal mRNA of Tenebrio molitor using a monoclonal antibody raised against an adult-specific cuticular antigen only present in the hard cuticle, was obtained after primer extension at the 5' end. From this cDNA sequence, the deduced protein encompasses 199 amino acids (including a signal peptide) with a total molecular weight of 20.7 kDa. The protein exhibits a bipartite structure: glycine-rich region located in its NH2-terminal part and a carboxy-termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 62 publications
2
16
0
Order By: Relevance
“…but a dramatic switch in gene expression is observed after the pupal-adult reprogramming, and these changes are prevented by application of the JH analogue [12]. We have used the differential display technique [13] to search for new JH target genes expressed in the epidermis of T. molitor.…”
Section: Introductionmentioning
confidence: 99%
“…but a dramatic switch in gene expression is observed after the pupal-adult reprogramming, and these changes are prevented by application of the JH analogue [12]. We have used the differential display technique [13] to search for new JH target genes expressed in the epidermis of T. molitor.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, insect development is characterized by a periodic renewing of the cuticle (moulting process), including periodic shedding of the old cuticle (ecdysis). In holometabolous insects, the adult stage is reached after two metamorphic moults (pupal and adult moults) ; these dramatic changes require a considerable shift in gene expression, which is mainly controlled by two hormones, moulting hormone or 20-hydroxyecdysone and juvenile hormone.The structure and composition of cuticles, either larval, pupal or adult, may be very different, as demonstrated in several species by electrophoretic analyses (Srivastava, 1970; Roberts and Willis, 1980a,b;Chihara et al, 1982;Sridhara, 1983). In Tenehrio molitor (Insecta Coleoptera), previous studies (Roberts and Willis, 1980a,b; Lemoine and Delachambre, 1986; Lemoine et al, 1990) have shown that larval and pupal cuticle protein patterns are very similar, in contrast to the adult pattern.…”
mentioning
confidence: 99%
“…The structure and composition of cuticles, either larval, pupal or adult, may be very different, as demonstrated in several species by electrophoretic analyses (Srivastava, 1970; Roberts and Willis, 1980a,b;Chihara et al, 1982;Sridhara, 1983). In Tenehrio molitor (Insecta Coleoptera), previous studies (Roberts and Willis, 1980a,b; Lemoine and Delachambre, 1986; Lemoine et al, 1990) have shown that larval and pupal cuticle protein patterns are very similar, in contrast to the adult pattern.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…RNA Isolation-Total RNA from tissues of the four main regions of the worm were extracted by the phenol/chloroform/isoamyl alcohol method as described previously (20). Poly(A)-rich RNA were purified by affinity with oligo(dT)-cellulose (21).…”
Section: /Ebi Data Bank With Accession Number(s) Af266752mentioning
confidence: 99%